2014
DOI: 10.1002/pro.2409
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional structure of a sugar N‐formyltransferase from Francisella tularensis

Abstract: N-formylated sugars have been observed on the O-antigens of such pathogenic Gram-negative bacteria as Campylobacter jejuni and Francisella tularensis. Until recently, however, little was known regarding the overall molecular architectures of the N-formyltransferases that are required for the biosynthesis of these unusual sugars. Here we demonstrate that the protein encoded by the wbtj gene from F. tularensis is an N-formyltransferase that functions on dTDP-4-amino-4,6-dideoxy-D-glucose as its substrate. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 18 publications
4
58
0
Order By: Relevance
“…8,10 These enzymes function on dTDP-4-amino-4,6-dideoxyglucose (dTDP-Qui4N). Whereas their overall active site architectures are similar to WlaRD, QdtF, and FdtF, their quaternary structures are remarkably different as can be seen in the ribbon representation for VioF in Figure 7c.…”
Section: Resultsmentioning
confidence: 99%
“…8,10 These enzymes function on dTDP-4-amino-4,6-dideoxyglucose (dTDP-Qui4N). Whereas their overall active site architectures are similar to WlaRD, QdtF, and FdtF, their quaternary structures are remarkably different as can be seen in the ribbon representation for VioF in Figure 7c.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, they tend to be found in the O-antigens of such pathogenic organisms as Brucella abortus , Providencia alcalifaciens O40, Francisella tularensis , and Campylobacter jejuni (Ovchinnikova et al, 2012; Thoden et al, 2013; Wu and Mackenzie, 1987; Zimmer et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Since 2013, the three-dimensional structures of four sugar N -formyltransferases have been reported from this laboratory (Genthe et al, 2015; Thoden et al, 2013; Woodford et al, 2015; Zimmer et al, 2014). Two of these enzymes act upon dTDP-3-amino-3,6-dideoxyglucose (dTDP-Qui3N) whereas the other two utilize dTDP-4-amino-4,6-dideoxyglucose as a substrate (dTDP-Qui4N).…”
Section: Introductionmentioning
confidence: 99%
“…The overall three-dimensional structures of WbtJ and VioF were reported in 2014 and 2015, respectively, and their quaternary structures are decidedly different from that observed for WlaRD as can be seen in Figure 5a [8,24•]. As in WlaRD, the N-terminal domains of WbtJ and VioF harbor the active site region.…”
Section: Structures Of the N-formyltransferases From F Tularensis Anmentioning
confidence: 97%
“…Recent research has demonstrated, for example, that the O-antigens of some Gram-negative bacteria contain quite remarkable formylated dideoxysugars including 3-formamido-3,6-dideoxy-D-glucose (Qui3NFo), 3-formamido-3,6-dideoxy-D-galactose (Fuc3NFo), 4-formamido-4,6-dideoxy-D-glucose (Qui4NFo), and 4-formyl-D-perosamine as depicted in Figure 1b [4]. These unusual sugars have been found on such organisms as Brucella abortus [5], Salmonella enterica O60 [6], Providencia alcalifaciens O40 [7], Francisella tularensis [8], and Campylobacter jejuni [9]. Strikingly, all of the above organisms are extremely pathogenic.…”
Section: Introductionmentioning
confidence: 99%